Seismic vulnerability and failure modes simulation of ancient masonry towers by validated virtual finite element models. (November 2015) - Preciado, Adolfo
Abstract: Seismic protection of ancient masonry towers is a topic of great concern among the scientific community. A methodology for the seismic vulnerability assessment of all types of towers and slender unreinforced masonry structures (e.g., light houses and minarets) is presented. The approach is developed by four validated 3D FEM models representative of European towers. The models are subjected to linear elastic investigations to establish load carrying capacity and dynamic properties for validation against similar towers. Seismic simulations are developed through intensive nonlinear static pushover analyses. From the assessments, the failure modes and overall seismic response of the towers are obtained. Low tensile strength of masonry and large openings at belfries have significant influence on the seismic behavior, resulting in a quasi-brittle failure. All the towers presented an imminent high vulnerability to seismic actions. The few investigations reported in literature on the seismic behavior of towers are focused on in-plane behavior, disregarding out-of-plane behavior and toe crushing, both aspects are investigated in this paper. The more flexible towers are close to present toe crushing in both planes. The failure mechanisms are validated with reported post-earthquake observations on real damaged towers. Highlights: A method for the seismic vulnerability assessment of slender URM structures The seismic failure and behavior of four validated virtual towers are simulated The numerical failure modes are in good agreement with post-earthquake observations Advantages and disadvantages through the seismic analysis process are discussed Seismic coefficients are in good agreement and typical of old masonry towers